Heterologous Expression of Immature Forms of Human Islet Amyloid Polypeptide in Yeast Triggers Intracellular Aggregation and Cytotoxicity - Raimundo, Ana F.; Ferreira, Sofia; Farrim, Maria I.; Santos, Cláudia N.; Menezes, Regina (Frontiers in Microbiology, 2020)
Diabetes is a major public health issue that has attained alarming levels worldwide. Pancreatic aggregates of human islet amyloid polypeptide (IAPP) represent a major histopathological hallmark of type 2 diabetes. IAPP is expressed in β-cells as pre-pro-IAPP (ppIAPP) that is first processed to pro-IAPP (pIAPP) and finally to its mature form (matIAPP), being released upon glucose stimulation together with insulin. Impairment and overload of the IAPP processing machinery seem to be associated with the accumulation of immature IAPP species and the formation of toxic intracellular oligomers, which have been associated with β-cell dyshomeostasis and apoptosis. Nevertheless, the pathological importance of these immature IAPP forms for the assembly and cytotoxicity of these oligomers is not completely understood. Here, we describe the generation and characterization of unprecedented Saccharomyces cerevisiae models recapitulating IAPP intracellular oligomerization. Expression of green fluorescent protein (GFP) fusions of human ppIAPP, pIAPP, and matIAPP proved to be toxic in yeast cells at different extents, with ppIAPP exerting the most deleterious effect on yeast growth and cell viability. Although expression of all IAPP constructs induced the formation of intracellular aggregates in yeast cells, our data point out the accumulation of insoluble oligomeric species enriched in immature ppIAPP as the trigger of the high toxicity mediated by this construct in cells expressing ppIAPP-GFP. In addition, MS/MS analysis indicated that oligomeric species found in the ppIAPP-GFP lysates contain the N-terminal sequence of the propeptide fused to GFP. These models represent powerful tools for future research focused on the relevance of immature forms in IAPP-induced toxicity. Furthermore, they are extremely useful in high-throughput screenings for genetic and chemical modulators of IAPP aggregation.